Variação na concentração de carboidratos não estruturais e polímeros de parede celular em espécies arbóreas de uma floresta de restinga - Volponi, Fabiano Caprini (2018)
The environmentally heterogeneous restinga forests provide an excellent opportunity to the investigation of the seasonal dynamics of non-structural carbohydrate and cellwall polymers, which are considered most abundant biomolecules in nature. This study was performed in a patch of restinga florest at Paulo Cesar Vinha State Park, Guarapari municipality of Espirito Santo State, whose plant communities are distributed along three contrasting sites across a steep flooding gradient [periodically floodable (PF), transition (TR), and non-floodable (NF)]. Such a strong environmental gradient reflect in the occurrence of restrict (only found in one site) and widely distributed wood plant species throughout the study area. The goal of this study it was evaluate the non-structural carbohydrates contents (glucose, fructose, sucrose and starch) and cell-wall polymers (cellulose, hemicellulose and lignin) in branches, trunks and leaves of individuals of Eugenia bahiensis (NF site abundant), Guarea macrophylla (TR site abundant), Calophyllum brasiliense (PF abundant) and Protium icicariba widely spreaded out along the three sites. This dissertation it was organized in two chapters. In the first one it was investigated the variation on content of carbon biomolecules in a P. icicariba population distributed throughout the three forest areas. Consistent differences were found between the NF and PF zones. Leaves of individuals of NF’s zone showed higher content of sucrose, starch and hemicellulose in relation to those of PF. On the other hand, higher content of cellulose and lignin were observed in leaves of individuals in the PF zone. The variation of non-structural carbohydrates and cell-wall polymers have been mainly associated to water availability, and likely the influence of soil nutrients content, parasitism and herbivory. In the second chapter, was studied the seasonal effect (winter and summer) over the carbon biomolecules carbon in vegetative organs (stems, branches and leaves) of C. brasiliense, G. macrophylla and E. bahienses. Hemicelluloses content were higher on winter and lower on summer season, regardless of species and organ. Sucrose contents in leaves were higher during the summer. The cellulose and lignin molecules didn’t exhibit consistent variation, being more influenced by the content variation of other molecules. The remobilization of reserve molecules, mainly hemicellulose, were recorded during the summer, and was associated with an increase of the energy demand to underlie the reproductive growth.